Luangwa – the valley of the leopard: - Riffel, Michael; Riffel, Tom (Biologie in unserer Zeit, 2022)
The Luangwa Valley in Eastern Zambia is one of the last big African natural landscapes with largely intact habitats. Due to its special climatic status as a dry area, it acts as a bridge habitat between the dry savannahs of Eastern and Southern Africa in the middle of the Miombo forest belt. In this distribution area, this is manifested in a range of animal species and in the tendency towards the taxonomic independence of individual species such as the Luangwa giraffe and the Cookson’s wildebeest. The area is protected by several national parks. The pandemic and the associated travel restrictions led to a collapse in tourism and negative consequences for the local population and wildlife. The essential role of tourism in the long-term preservation of these important large habitats is emphasized.